Cell Vacuolation, a Manifestation of the El Tor Hemolysin of Vibrio cholerae - Mitra, Rupak (American Society for Microbiology, 2000)
Culture supernatants of nontoxigenic nonepidemic clinical strains of Vibrio cholerae belonging to diverse serogroups were found to induce vacuolation of nonconfluent HeLa cells. The vacuoles became prominent 18 h after introduction of culture supernatant, and vacuolated cells survived for 48 h and then died. Only a fraction of the vacuolated cells took up neutral red dye, implying that there were differences in the vacuolar microenvironment. Further tests showed that the factor responsible for vacuolation was heat labile and proteinaceous. Vacuolating activity was completely neutralized by antibody to hemolysin of V. cholerae but not by antibody to vacuolating cytotoxin of Helicobacter pylori. Partial purification of the vacuolating factor led to elution of fractions, which showed both hemolytic and vacuolating activity. PCR amplification and cloning of the hemolysin structural gene (hlyA) into Escherichia coli DH5α led to isolation of clones producing cell vacuolating factor in a cell-associated form. Further, a null insertion mutation in the hlyA gene of a high-vacuolating-factor-producing strain led to complete abolition of both cell vacuolating and hemolytic activities. These analyses establish vacuolation as a potentially important but previously unrecognized property of V. cholerae El Tor hemolysin.